دور المراجعين الداخليين في تقييم وتحسين فاعلية إدارة مخاطر منظمات الأعمال " دراسة تطبيقية على الإدارات العامة وإدارات المناطق بالمصارف التجارية في نطاق مدينة بنغازي" (Economic studies journal, 2022)
The study aims to identify the role of internal auditors in assessment of business's risk management in general. It also attempts to obtain empirical evidence from the staff of commercial banks general managements and the managements within Benghazi districts in particular.The study adopted deductive and inductive method, known as the modern scientific method, in accounting. The technique used by U.S Accounting Standards Board (ASB) since its establishment in 1973. It is also the method used in many similar studies in Libyan universities.A questionnaire was utilized as an instrument of collecting relevant data for hypotheses test. The study hypotheses and questionnaire questions articulated according to the theoretical framework and related literature. In gathering the questionnaire parts, close-questions of an open end were used to capitalize on close questions advantages and avoid their disadvantages.The study sample consisted of auditing committees' members, auditors of internal auditing departments and risk managements of commercial banks that operate in Benghazi city, auditors of in department of banks and money monitoring in Libyan central bank, and private external auditors registered in Libyan central bank.The study used constancy analysis to verify the steadiness of questionnaire questions and its conformity to the study objectives. It also used descriptive statistics to determine the trend of participants' responses and inductive statistics (uni - variation analysis) to identify the basic differences in participants' responses at significance level of 0.05%, assuming that the data was normally distributed. If there were essential discrepancies, multiple comparisons would be collected to determine the group (s) that crucially differs from other groups. For hypotheses test,      T-test per sample was utilized.The study revealed that internal auditors have an essential role in evaluating risk management of commercial banks working in Benghazi city. However, comparison of statistical analysis (scientific conclusions) by its theoretical conclusions results (study hypotheses), so-called induction, has shown that theoretical and scientific conclusions of the study were matched. Therefore, the study added scientific evidence from local environment support its literature and augmented its theoretical conclusions.